Design and convective calibration of a transverse heat flux sensor. Issue 2 (3rd March 2016) - Meier, T.; Stathopoulos, P.; von Rohr, Ph. Rudolf
Abstract : In this work, a transverse heat flux sensor built from alternating layers of K-Type thermocouple materials is presented. In the first step, the sensor is calibrated in radiation heat transfer, and its behavior is compared to existing sensors found in the literature. Subsequently, a secondary calibration is performed in a stagnation heat transfer facility, where surface temperatures up to 400°C and heat flux up to 550 kW/m 2 are achieved. The radiative sensitivity is found to be 1.35 μV m 2 /kW, while in a convective environment, the value varies between 0.8 and 1.8 μV m 2 /kW. This difference is attributed to the temperature-dependent material properties and the angle formed by the heat flux and the surface of the anisotropic material. The experimental sensitivities compare well with a parametric model able to account for this angle. Eventually, we emphasize the use of transverse sensors for stagnation heat transfer investigations, especially for applications where chemical compatibility and mechanical robustness are required.